Pengaruh Struktur Kepemilikan dan Profitabilitas terhadap Manajemen Laba pada Consumers Cyclical Industry - Adira Annastasia Boewono; Sufiyati (Masyarakat Ekonomi Syariah Bogor, 2024)
Publication and disclosure of information to the general public are of particular concern to management because the company wants to show good performance and image that will have a long-term impact on the company. The component in the financial report that is first highlighted by stakeholders is related to profit. Thus, companies often take profit management actions only to manipulate profits as a reflection of good company performance. Many factors influence companies to carry out profit management such as ownership structure and company profitability. The study aims to examine the effect of managerial ownership, institutional ownership, and profitability on profit management in the non-primary goods industry listed on the IDX in 2018-2022. The sample uses data from 47 companies from a total population of 151 companies. The study uses descriptive statistics with quantitative methods. So, this study is a secondary study because the data used in the study uses data from the company's financial statements and annual reports. Sampling using purposive sampling because there are established criteria. The results of the study state that there is a significant influence of managerial ownership and institutional ownership on profit management. Meanwhile, the profitability variable does not have a significant influence on profit management.